2016
DOI: 10.1016/j.jtcvs.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The 3 R's: The radial artery, the right internal thoracic artery, and the race for the second best

Abstract: We discuss the meta-analysis performed by Benedetto and colleagues of propensitymatched observational studies comparing the right ITA versus the radial artery as the second arterial conduit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In addition, much of the vein's outermost layer, the adventitia, is also removed or damaged. In C artery (RA) [8][9][10] . Apart from the structural differences between arteries and veins, it is noteworthy that, in general, LITA and RA are harvested in such a way that the pedicle of the surrounding tissue remains intact.…”
Section: Saphenous Vein Structure and Vascular Damagementioning
confidence: 99%
“…In addition, much of the vein's outermost layer, the adventitia, is also removed or damaged. In C artery (RA) [8][9][10] . Apart from the structural differences between arteries and veins, it is noteworthy that, in general, LITA and RA are harvested in such a way that the pedicle of the surrounding tissue remains intact.…”
Section: Saphenous Vein Structure and Vascular Damagementioning
confidence: 99%
“…The radial artery has also been widely investigated as a potential conduit for CABG. Unfortunately, the results of these investigations have been mixed at best, and contradictory at worst (21). For example, the Radial Artery Patency Study (RAPS) demonstrated superior rates of patency at 1-year for the radial artery as compared to saphenous vein grafts (22), but a VA Cooperative RCT found no difference in 1-year patency between these same options (23).…”
Section: Multiple Arterial Graftingmentioning
confidence: 99%
“…However, because BITA grafting was also associated with increased risk of DSWI, we recommended that it be used in diabetic patients whose risk of DSWI is low. The RA is another commonly used arterial graft conduit that has been shown to be associated with better clinical and angiographic outcomes than vein grafts [13,14]. Therefore, we sought to determine in diabetic patients whether SITA plus RA grafting yields outcomes similar to those of patients who undergo BITA grafting.…”
Section: Introductionmentioning
confidence: 99%